Validation of resilient and drought adapted forage options for mixed farming systems in Northern Ghana - Ansah, Terry; Pigangsoa Konlan, Solomon; Cudjoe, Shedrack; Akufo, Naana M.; Mogre, Joshua W.S.; Dari, Prosper S.; van der Hoek, Rein (2024)
This study evaluates the biomass yield and chemical composition of different grass species harvested at three intervals across the years 2023 and 2024 at two sites at the Nyankpala campus of the University of Development Studies in Tamale, Ghana. Twelve grass and legumes were assessed, including Panicum maximum (Megathyrsus maximus) cv Massai, P. Mombasa, Cenchrus purpureus, and various Brachiaria (Urochloa) hybrids and cultivars. The highest biomass yields were recorded for P. Massai, P. Mombasa, P. Mun River and B. Camello, while B. Basilisk showed the lowest yield. P. Massai and P. Mombasa exhibited moderate to high protein content, while Cenchrus purpureus had high total digestible nutrients but lower protein levels. The Brachiaria grasses generally displayed a higher fiber content, particularly B. Hybrid GP0423. The data suggest that P. Massai and P. Mombasa are particularly suitable for high-biomass production, while species like Cenchrus purpureus offer a balance of high digestibility with moderate protein content. The results emphasize the need to select grass species based on yield, nutritional composition and drought resilience to optimize forage production for various agricultural and livestock needs. On-farm trials with P. Mun River showed good results and farmers are encouraged to integrate Panicum Mun River and the other well performing forages into their mixed farming system to increase high quality feed availability and improve system resiliency.